2010
DOI: 10.1186/1476-4598-9-264
|View full text |Cite
|
Sign up to set email alerts
|

Frequent epigenetic inactivation of RASSF2 in thyroid cancer and functional consequences

Abstract: BackgroundThe Ras association domain family (RASSF) encodes for distinct tumor suppressors and several members are frequently silenced in human cancer. In our study, we analyzed the role of RASSF2, RASSF3, RASSF4, RASSF5A, RASSF5C and RASSF6 and the effectors MST1, MST2 and WW45 in thyroid carcinogenesis.ResultsFrequent methylation of the RASSF2 and RASSF5A CpG island promoters in thyroid tumors was observed. RASSF2 was methylated in 88% of thyroid cancer cell lines and in 63% of primary thyroid carcinomas. RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 35 publications
1
50
0
Order By: Relevance
“…They also observed that gastric cancers with methylation at U1 and D1 exhibited significantly less frequent lymphatic permeation than unmethylated gastric cancers. Afterwards, epigenetic inactivation of RASSF2 was found in oral squamous cell carcinoma (16), head and neck squamous cell carcinoma (26), hepatocellular (27) and thyroid cancers (28). Although a previous study demonstrated that expression of the RASSF2 gene is silenced by methylation in human gastric cancer (29), the authors did not clarify the clinical impact of RASSF2 expression or the prognostic value for patients with gastric cancer since the number of cases was too small.…”
Section: Discussionmentioning
confidence: 65%
“…They also observed that gastric cancers with methylation at U1 and D1 exhibited significantly less frequent lymphatic permeation than unmethylated gastric cancers. Afterwards, epigenetic inactivation of RASSF2 was found in oral squamous cell carcinoma (16), head and neck squamous cell carcinoma (26), hepatocellular (27) and thyroid cancers (28). Although a previous study demonstrated that expression of the RASSF2 gene is silenced by methylation in human gastric cancer (29), the authors did not clarify the clinical impact of RASSF2 expression or the prognostic value for patients with gastric cancer since the number of cases was too small.…”
Section: Discussionmentioning
confidence: 65%
“…RASSF2 has previously been shown to be methylated in various cancers including breast, colorectal, gastric, lung, oral and thyroid cancer. [8][9][10][11][12] Expression of RASSF2 was found to be an independent prognostic factor in gastric cancer patients 10 and RASSF2 methylation could be detected in fecal DNA from patients with gastrointestinal tumors. 13 In functional terms RASSF2 is a novel pro-apoptotic effector of K-Ras and acts as a tumor suppressor gene.…”
Section: Methodsmentioning
confidence: 96%
“…Expression primers used in RT-PCR were previously described by reference 19. The real time RT-PCR primers for RASSF2 were described in Schagdarsurengin U et al 11 and human ÎČ actin primers were described in. 21 Power SYBR Green mix (Applied Biosystems) was used and the plates were read using BIO-RAD IQ5 machine.…”
Section: Supplemental Materialsmentioning
confidence: 99%
“…Inhibits cell growth, arrests cell cycle [58,62] Involved in actin cytoskeleton organization [148] Induces apoptosis [58,62,145] Suppresses transcriptional activity of NFjB [181] Inhibits MST2 activity [93] K-Ras [62] PAR4 [64] MST1 [66,177] MST2 [177] Yes [67] growth retardation, systematic haematopoietic anomalies, defects in osteoclast and osteoblast differentiation 3 12q14. 1 …”
Section: Rassf1amentioning
confidence: 99%